Potential effects of valproate and oxcarbazepine on growth velocity and bone metabolism in epileptic children- a medical center experience. Issue 1 (December 2016) - Lin, Chien-Ming; Fan, Hueng-Chuen; Chao, Tsu-Yi; Chu, Der-Ming; Lai, Chi-Chieh; Wang, Chih-Chien; Chen, Shyi-Jou
Abstract Background Children with longstanding use of antiepileptic drugs (AEDs) are susceptible to developing low bone mineral density and an increased fracture risk. However, the literature regarding the effects of AEDs on growth in epileptic children is limited. The aim of this study was to investigate the potential effects of valproate (VPA) and/or oxcarbazepine (OXC) therapy on growth velocity and bone metabolism. Methods Seventy-three ambulatory children (40 boys and 33 girls) with epilepsy, aged between 1 and 18 years (mean age 9.8 ± 4.1 years), were evaluated for growth velocity before and for 1 year after VPA and/or OXC treatment. The bone resorption marker serum tartrate-resistant acid phosphatase 5b (TRAcP5b) and the bone formation marker serum bone-specific alkaline phosphatase (BAP) were measured post-AEDs therapy for 1 year. Results The difference in growth velocity (ΔHt) and body weight change (ΔWt) between pre- and post-AEDs treatment were -1.0 ± 2.8 cm/year (P  < 0.05) and 0.1 ± 3.9 kg/year (P  = 0.84), respectively. The study population had serum TRAcP5b-SDS of -1.6 ± 1.2 and BAP-SDS of 1.7 ± 3.7 compared with sex- and age-matched healthy children. Significant correlation between serum TRAcP 5b and BAP activities was noted (r  = 0.60, p  < 0.001). There was a positive correlation between growth velocity and serum TRAcP 5b activity after AED treatment (r  = 0.42, p <  0.01). No correlation was found between ΔHt, ΔWt, serum TRAcP 5b, BAP activity and types of AEDs. Conclusion Growth velocity was significantly decreased in epileptic children after 1 year of VPA and/or OXC treatment. The effect of VPA and/or OXC therapy on dysregulation of bone metabolism might play a crucial role in physical growth.